PERANCANGAN KAPAL BULK CARRIER 19000 DWT DENGAN KECEPATAN 12 KNOT SEBAGAI PENGANGKUT BATUBARA UNTUK RUTE PELAYARAN LAMPUNG - SURABAYA - Ihsanul Ridho, (2020)
Bulk carrier ship is a type of vessel specifically designed for transporting bulk cargo or unpackaged cargo. Cargo that can be transported by bulk carrier vessels such as grains, limestone, iron ore, iron sand, coal, etc. Bulk carrier ship is the right solution to overcome the distribution of coal, whose demand is increasing to several steam power plants (PLTU) in Indonesia. Therefore, in line with the needs of the market, especially in connection with the implementation of the 5-year inpres 2005 about the empowerment of national shipping industry and 17 years of 2008 about the cruise, the author devised bulk carrier A coal-charged bulk carrier the needs at Paiton (PLTU) steam power Plant, East Java. The ship-size Search process becomes the first thing done before the ship building process. The ship's design is done using several methods: Comparison method, trial method, and literacy method. Thus This method is diobtained by ship design with the main size , namely length, width, height and loaded based on the desired vessel capacity and form coefficient. In this design obtained the main size of the vessel LOA = 143.66 m, LWL = 142.05 m, lpp = 137.91 m, B = 22.32 m, H = 12.38 m, T = 9.25 m. From the hydrostatic calculation obtained displacement = 23382.99669 ton, Cb = 0.8. In the calculation of stability, the results showed that the bulk carrier has good stability because the point M is above the point G in all conditions. To the end of the general plan picture, the bulk carrier ship has a loading space that can accommodate approximately 19000 tons. The obstacles experienced the bulk carrier ship at the speed of 12 knots and require a 7000 HP mains engine power.